If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-15=x-23
We move all terms to the left:
3x-15-(x-23)=0
We get rid of parentheses
3x-x+23-15=0
We add all the numbers together, and all the variables
2x+8=0
We move all terms containing x to the left, all other terms to the right
2x=-8
x=-8/2
x=-4
| X³+8x²+16=0 | | -8a-4=-9a+1 | | 5m=5-2m | | 5+3x=5x-10 | | 11m^2-11m=6 | | 2x+33=5x-6 | | 3x-15=15x-23 | | 5^x=83 | | -12x-3=-9x-9 | | X^2-7x-58=0 | | X^-7x-58=0 | | 37+3x+47=5x+62 | | 0=0.05v^2+1.2v-200 | | 8-5x=4x=-10+x | | 28=12+4r | | 18-2g=4g+0 | | 7x+14=9x+10 | | -a^2+13a-30=0 | | 8x+39=11x+18 | | 6x+63=6x | | 7x+26=10x+2 | | -19.66-0.5g=13.7g+19.54-11.4g | | 7(k−6)=21 | | 9x-46=4x-6 | | 10(g+8)=260 | | 20n=19n-9 | | 8(d+9)=88 | | -q−10=10+9q | | 5c-9+1c=2c-73 | | 3y+1=4(-6+2y) | | -6b+8=-9b−4 | | -2t=-t−5 |